PENGARUH PERSEPSI PELAKSANAAN SENSUS PAJAK NASIONAL, SIKAP WAJIB PAJAK PADA PELAKSANAAN SANKSI DENDA DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK ORANG PRIBADI DI KELURAHAN MIJI KOTA MOJOKERTO) - FAJRIYAN, Nur AFIANTI (Jurnal Mahasiswa Perpajakan, 2015)
Tax compliance is one of  factors in achieving revenue goals through taxation sector. Direktorat Jenderal Perpajakan (DJP) as the government agencies that provide services in the field of taxation is trying to create a program of the National Tax Census aimed to obtain accurate data on the taxpayer, which is expected to increase tax compliance. Taxation system applied in Indonesia  is a self-assessment system in which the system gives occasion to the taxpayers to calculate, pay and report how much the tax that they must pay to government. The application of this system is accompanied by supervision by DJP with the provision of financial penalties, so that the attitude of the taxpayer on the implementation of the financial penalties are expected to increase the level of tax compliance if the taxpayer considers that the penalties would be more burdensome tax burden. The application of the system of self-assessment system that gives authority entirely to the taxpayer to calculate the tax itself is not handled from the necessity of taxation public awareness as to the importance of tax taxpayer for the governance and national development.  Miji subdistric Mojokerto City known as one of the craft center and miniature of Phinisi boat, some people who live in the area  work as a craftsman shoe so that the public is obliged to be a taxpayer and report their income. Potential tax in Miji subdistric Mojokerto city make the place become one of the main objectives of the National Tax Census program. Keywords: Implementation of National Tax Census Perception, Attitudes Taxpayers toward the Implementation of Sanction Fines, Consciousness Taxation, Taxpayer Compliance.